Impedance effect of elliptical curved surface on RFID tag performances - Suwalak, Rattapong; Phongcharoenpanich, Chuwong (My University, 2017)
This paper presents the effect of the impedance curved surface to the characteristics of the RFID tag. The proposed passive RFID tag is placed on the elliptical curved surface. From the simulation result, it this found that the proposed RFID tag has a flat gain in the UHF RFID frequency band in Thailand. Moreover, the variation of the length and width of the elliptical surface is important effect on the input reactance of the RFID tag.
Keywords: curving; impedance surface; RFID tag; UHF